Factors Affecting Mother’s Behavior in Doing Infant Massage Independently in the Dian Maternal Clinic in Jakarta Barat in 2022 - Ericha Merammis BR Sembiring; Basaria Manurung; Dewi Purba; Nurmala Sari Dewi; Elfiana (Institute of Computer Science (IOCS), 2022)
In the midst of this developing society, people in Indonesia still use traditional health services, especially baby massage to traditional birth attendants. Baby massage to a shaman has become a hereditary tradition. This study aims to determine the factors that influence the behavior of mothers in doing baby massage independently at the Dian Maternity Clinic, West Jakarta. This type of research is an analytical survey. Then analyze the dynamics of the correlation between phenomena or between risk factors and effect factors is a phenomenon that results in an effect (influence). There is no influence between the mother’s education factor on the mother’s behavior in doing baby massage independently at the Dian Maternity Clinic in 2022 with a p value of 0,580. There is no influence between the mother’s knowledge factor with a p value of 0,551. There is an influence between the mother’s attitude factor on the mother’s behavior with a p value of 0,021.